2020
DOI: 10.1101/2020.04.30.070714
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Patterning of Irritability Enhances Prediction of Psychopathology in Pre-adolescence: Improving RDoC with Developmental Science

Abstract: Research has demonstrated the transdiagnostic importance of irritability in psychopathology pathways but the contribution of developmentally-unfolding patterns has only recently been explored. To address this question, irritability patterns of 110 youth from a large and diverse early childhood cohort were assessed at preschool age and at school age (~2.5 years later) with a dimensional irritability scale designed to capture the normal:abnormal spectrum.Participants then returned at Pre-adolescence (~6 years la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In other words, children with high and stable levels of irritability in preschool (M age = 4.17 years) and elementary school (M age = 6.95 years) were reported to show more externalizing behavior in pre-adolescence. In contrast, children with high but decreasing levels of irritability across these time points displayed more internalizing behavior in pre-adolescence (Damme et al, 2021). Together, these findings suggest that clinical prediction may be improved when the developmental course of irritability is taken into consideration.…”
Section: Irritability: a Trait Antecedent Of Frustrative Nonrewardmentioning
confidence: 88%
See 2 more Smart Citations
“…In other words, children with high and stable levels of irritability in preschool (M age = 4.17 years) and elementary school (M age = 6.95 years) were reported to show more externalizing behavior in pre-adolescence. In contrast, children with high but decreasing levels of irritability across these time points displayed more internalizing behavior in pre-adolescence (Damme et al, 2021). Together, these findings suggest that clinical prediction may be improved when the developmental course of irritability is taken into consideration.…”
Section: Irritability: a Trait Antecedent Of Frustrative Nonrewardmentioning
confidence: 88%
“…Importantly, the type, frequency, and intensity of the behaviors tend to manifest differently over the first 5 years of life, both within and between individuals (e.g., Denham, Lehman, & Moser, 1995;Eisenberg et al, 1997;Liu et al, 2018). Capturing these variations may help to identify patterns associated with later psychopathology (e.g., Damme, Wakschlag, Briggs-Gowan, Norton, & Mittal, 2021). Using a person-centered approach, Perra, Paine, and Hay (2020) found that, from 6 to 36 months of age, three subgroups of infants could be identified based on their levels of anger/aggressiveness.…”
Section: Irritability: a Trait Antecedent Of Frustrative Nonrewardmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk calculators predicting depression and ADHD in youth and young adults have also been tested, demonstrating c statistics above 0.7 in test samples (but poorer discrimination in some validation samples; e.g., Caye et al, 2020;Rocha et al, 2021). Research has also shown that some of the problem behaviors identified in these older age groups (e.g., the majority of severe and chronic internalizing and externalizing problems; Meehan et al, 2020;Damme, Wakschlag, Briggs-Gowan, Norton, & Mittal, 2021) onset with symptoms or vulnerability patterns in early childhood, laying the groundwork for identification far earlier in the developmental sequence (Wakschlag et al, 2018).…”
Section: Predicting Internalizing and Externalizing Problems In Early Childhoodmentioning
confidence: 99%
“…Studying these specific skills that have a strong relation with reading may provide greater mechanistic insight because they are more focused and dimensional than the general diagnostic category of dyslexia or grouping based on word reading scores. Researchers and leaders in the area of mental health have advanced a dimensional, symptoms-based approach (National Institute of Mental Health's Research Domain Criteria, or RDoC; Cuthbert and Insel, 2013) in order to parse heterogeneity in diagnostic categories, which are particularly varied in development (Mittal and Wakschlag, 2017;Damme et al, 2020) and ultimately, to better understand the neurobiology of disorders. Thus, in this study, we explicitly tested how MMN measures related to PA and RAN, two crucial reading-related skills and deficits in dyslexia.…”
Section: Introductionmentioning
confidence: 99%